The Grotesque and The Surreal in Gian Carlo Riccardi: Some Psychological Considerations (British Journal of Multidisciplinary and Advanced Studies, 2025)
The main purpose of this study is to analyse some graphic and pictorial works created in the 1970s by the Italian avant-garde artist Gian Carlo Riccardi (1933-2015). The main theme seems to be the grotesque representation of contemporary society and the individual victim of a homologising and apathetic humanity. This research intends to show how the artist's experiments are expropriated of an aesthetic function, to impose themselves as a traumatic and reactionary force, thus investigating the body and unconscious of the protagonists of his works, the drives, the collective and individual anxieties. Through a pictorial grammar that traces the contours of bodies with an incisive sign and vibrant colours, Gian Carlo Riccardi opens up space towards a transfiguration of reality. The artistic scenario expands its limits towards an illusory and disturbing vision, an architectural space formed by industrial relics and the detritus of a massified society that contaminates and penetrates man. The architectural landscape becomes a sort of theatre stage that opens the curtain on the human unconscious, its traumas and repressed and repressed desires. Gian Carlo Riccardi synthesises physical and moral decadence in the subjects that crowd his representations. The clowns and machine men are not a representation of the circus world, but a metaphor for contemporary society concealed behind a mask. The fairy tale and the dream of the surrealist works burst into the artist's works. Irrationality and the unconscious are constantly observed by Gian Carlo Riccardi, who through his graphic and pictorial works constantly intervenes in reality with an ironic gaze.